MOF‐Derived Porous Dodecahedron rGO‐Co3O4 for Robust Pulse Generation. Issue 5 (7th January 2022) - Li, Xiaohui; An, Mingqi; Li, Gang; Han, Yueheng; Guo, Penglai; Chen, Enci; Hu, Jiyi; Song, Zhuoying; Lu, Hongbing; Lu, Jiangbo
Abstract: As a member of the porous crystalline material family, metal organic framework (MOF) materials have been widely used in the fields of photodetection, photovoltaic cells, nonlinear optical devices, supercapacitors, and biological imaging. However, few reports about robust pulsed laser based on MOF‐derived nanomaterials especially the one with unique structure have been reported till now. In this paper, porous dodecahedron rGO‐Co3 O4 is synthesized by calcining the MOF template and systematically analyzed. Interestingly, the rGO‐Co3 O4 is successfully prepared as a saturable absorber (SA) by using the optical deposition method and the modulation depth of the rGO‐Co3 O4 SA is 8.38%. Through different dispersion management, robust pulses with 1.5 µm dissipative soliton (DS) in the frequency domain and square wave pulse (SWP) in the time domain can be obtained in the erbium‐doped fiber laser based on rGO‐Co3 O4 SA. The 3‐dB bandwidth and pulse duration of the DS are 6.81 nm and 62.01 ps, respectively. The pulse tuning range of the SWP is 1.24 ns ≈ 19.14 ns. It is worth mentioning that the threshold of the SWP is 53.72 mW, and the mode‐locked laser can be self‐started at the pump power of 72.04 mW. The experimental results show that the porous dodecahedral rGO‐Co3 O4 material derived from MOF can be used as an excellent nonlinear optical modulator, providing a new choice for material processing. Abstract : Metal organic framework (MOF)‐derived porous dodecahedron rGO‐Co3 O4 is a fascinating material with excellent nonlinear optical characteristics. Through different dispersion management, robust pulses with 1.5 mm dissipative soliton and square wave pulse can be obtained in the erbium‐doped fiber laser based on rGO‐Co3 O4 SA. This work expands the application fields of MOF and provides new choice for material processing.